A longitudinal study of the association between infrapatellar fat pad maximal area and changes in knee symptoms and structure in older adults. Issue 10 (15th May 2014) - Pan, Faming; Han, Weiyu; Wang, Xia; Liu, Zhenhua; Jin, Xingzhong; Antony, Benny; Cicuttini, Flavia; Jones, Graeme; Ding, Changhai
Abstract : Background: The infrapatellar fat pad (IPFP) is of uncertain significance for knee osteoarthritis. The aim of this study was to describe the longitudinal associations between baseline IPFP maximal area and changes in knee pain, knee cartilage volume and cartilage defects in older adults. Methods: 356 community-dwelling male and female adults aged 50–80 years were measured at baseline and approximately 2.6 years later. T1-weighted or T2-weighted fat-suppressed MRI was used to assess maximal IPFP area, cartilage volume and cartilage defects at baseline and/or follow-up. Knee pain was assessed by the self-administered Western Ontario McMaster Osteoarthritis Index questionnaire. Results: After adjustment for confounders, IPFP maximal area in women was significantly and negatively associated with changes in knee pain (β: −0.18 to −0.86 for total knee pain, pain at night while in bed, pain when sitting/lying and pain when standing upright, all p<0.05) but not with other knee pain subscales. IPFP maximal area in women was beneficially associated with change in tibial cartilage volume per annum (β: +1.56% per cm 2 at medial site; +0.86% per cm 2 at lateral site, both p<0.05), but not with change in patellar cartilage volume. Further, it was significantly associated with reduced risks of increases in medial cartilage defects (relative risk: 0·46 at tibial site, relative risk: 0.59 at femoral site; both p<0.05) but not with increases at other sites in women. No significant associations were found in men. Conclusions: While the associations are not fully consistent, IPFP maximal area appears to have a protective role for knee symptoms and cartilage damage in older female adults.